Time-dependent genetic effects on gene expression implicate aging processes - Bryois, Julien; Buil, Alfonso; Ferreira, Pedro G.; Panousis, Nikolaos I.; Brown, Andrew A.; Viñuela, Ana; Planchon, Alexandra; Bielser, Deborah; Small, Kerrin; Spector, Tim; Dermitzakis, Emmanouil T. (Genome Research, 2017)
Gene expression is dependent on genetic and environmental factors. In the last decade, a large body of research has significantly improved our understanding of the genetic architecture of gene expression. However, it remains unclear whether genetic effects on gene expression remain stable over time. Here, we show, using longitudinal whole-blood gene expression data from a twin cohort, that the genetic architecture of a subset of genes is unstable over time. In addition, we identified 2213 genes differentially expressed across time points that we linked with aging within and across studies. Interestingly, we discovered that most differentially expressed genes were affected by a subset of 77 putative causal genes. Finally, we observed that putative causal genes and down-regulated genes were affected by a loss of genetic control between time points. Taken together, our data suggest that instability in the genetic architecture of a subset of genes could lead to widespread effects on the transcriptome with an aging signature.
10.1101/gr.207688.116